IDDF2019-ABS-0069 Reduced expression of circRNA hsa_circ_001888 in gastric cancer and its clinical significance. (June 2019) - Shi, Peina; Song, Haojun; Ding, Xiaoyun
Abstract : Background: Circular RNAs (circRNAs) are a new class of endogenous noncoding RNAs. Owing to the special covalently closed loop structure without 5' end caps or 3' poly (A) tails, circRNAs are more stable and conserved than linear RNAs. Growing evidence shows that circRNAs play a crucial role in the occurrence and development of several human diseases, especially cancers. However, little is known about their expression and function in gastric cancer (GC). Methods: The hsa_circ_001888 levels in 114 paired GC tissues and adjacent non-tumor tissues, 48 plasma samples from patients with GC and 48 plasma samples from health controls were detected by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Then, the relationships between hsa_circ_001888 expression and the clinicopathological features of patients with GC were further analyzed. Finally, a receiver operating characteristic (ROC) curve was generated to evaluate the diagnostic value of hsa_circ_001888. Results: Hsa_circ_001888 was first found to be significantly down-regulated in GC tissues (p<0.001, (figure 1A, B )) and plasma samples from patients with GC (p<0.001, (figure 1C ). The higher ΔCt value indicates lower expression. Moreover, we analyzed their association with clinicopathological features of patients with GC. Clinicopathological features showed that hsa_circ_001888 level in GC tissues was correlated with differentiation and in GC plasma linked with CEA and CA199 expression. We did not further find any association between its levels with other clinicopathological features such as age, gender, invasion, lymphatic metastasis. To evaluate the potential diagnostic value, the ROC curve was used . The area under the ROC curve of has_circ_001888 in tissues and plasma were up to 0.654 and 0.662, respectively (figure 1D ), suggesting good diagnostic value. Conclusions: These results indicated that hsa_circ_001888 was significantly down-regulated in GC and may serve as a novel potential biomarker in the diagnosis of GC.